Effects of Moderate Nitrate and Low Sulphate Depositions on the Status of Soil Base Cation Pools and Recent Mineral Soil Acidification at Forest Conversion Sites with European Beech (“Green Eyes”) Embedded in Norway Spruce and Scots Pine Stands - Florian Achilles (Forests, 2021)
High N depositions of past decades brought changes to European forests including impacts on forest soil nutrition status. However, the ecosystem responses to declining atmospheric N inputs or moderate N depositions attracted only less attention so far. Our study investigated macronutrient (N, S, Ca2+, Mg2+, K+) pools and fluxes at forest conversion sites over 80 years old in Central Germany with European beech (so-called “Green Eyes” (GE)). The GE are embedded in large spruce and pine stands (coniferous stands: CS) and all investigated forest stands were exposed to moderate N deposition rates (6.8 ± 0.9 kg ha−1 yr−1) and acidic soil conditions (pHH2O < 4.7). Since the understanding of forest soil chemical and macronutrient status is essential for the evaluation of forest conversion approaches, we linked patterns in water-bound nutrient fluxes (2001–2018) and in predicted macronutrient storage in the herbaceous and tree layer to patterns in litter fall (2016–2017) and in forest floor and mineral soil macronutrient stocks at GE and CS assessed in 2018. Our results exhibited 43% (Nt) and 21% (S) higher annual throughfall fluxes at CS than at GE. Seepage water at 100 cm mineral soil depth (2001–2018) of CS is characterized by up to fivefold higher NO3− (GE: 2 ± 0.7 µmolc L−1; CS: 9 ± 1.4 µmolc L−1) and sevenfold higher SO42− (GE: 492 ± 220 µmolc L−1; CS: 3672 ± 2613 µmolc L−1) concentrations. High base cation (∑ Ca2+, Mg2+, K+) concentrations in CS mineral soil seepage water (100 cm depth: 2224 ± 1297 µmolc L−1) show significant positive correlations with SO42−. Tree uptake of base cations at GE is associated especially with a Ca2+ depletion from deeper mineral soil. Foliar litter fall turns out to be the main pathway for litter base cation return to the topsoil at GE (>59%) and CS (>66%). The litter fall base cation return at GE (59 ± 6 kg ha−1 yr−1) is almost twice as large as the base cation deposition (30 ± 5 kg ha−1 yr−1) via throughfall and stemflow. At CS, base cation inputs to the topsoil via litter fall and depositions are at the same magnitude (24 ± 4 kg ha−1 yr−1). Macronutrient turnover is higher at GE and decomposition processes are hampered at CS maybe through higher N inputs. Due to its little biomass and only small coverage, the herbaceous layer at GE and CS do not exert a strong influence on macronutrient storage. Changes in soil base cation pools are tree species-, depth- and might be time-dependent, with recently growing forest floor stocks. An ongoing mineral soil acidification seems to be related to decreasing mineral soil base cation stocks (through NO3− and especially SO42− leaching as well as through tree uptake).